Raising Political Awareness and Journalist Ethics: Study of Muhammad Abduh’s Role through al-Waqa’i‘ al-Misriyyah - Amir, Ahmad Nabil; Rahman, Tasnim Abdul (Institute of Research and Public Service Universitas Jenderal Soedirman, 2025)
Role of Muhammad Abduh (1849-1905) in the publication of al-Waqā’i‘ al-Misrīyya (الوقائع المصرية, Egyptian Events) an official Egyptian gazette. It had a profound impact on the field of journalism in the context of the rising popularity of al-Waqā’i‘ al-Misrīyyah during his editorship (1880-1882), establishing its reputation as the leading Egyptian newspaper. His illustrious article highlights the establishment's unprecedented socio-cultural and religious reform, amid phenomenal and competitive growth of independent press. His writing was instrumental in developing national consciousness toward modernization programs and influencing public opinion in Egypt. It allowed for better development of formidable national spirit and awakening of their higher ideal and convention in language, literature, and culture, as well as mobilizing social awareness of intense political and cultural dynamics. His career spanned the period of Riyad Pasha and Sharif’s administration and subsequent political unrest. The research is based on qualitative and documentation techniques. It reviewed accumulated data by way of descriptive, analytical, historical, and comparative methods. The finding shows that al-Waqā’i‘ has assumed unprecedented influence and success during the editorship of Abduh through his dynamic and productive articles and rigorous daily basis of production of the newspaper that helps to raise public issues and concern and attract awareness of the global political situation as well as defending the significance value, norms, and ethics of journalism.